Proteomic analysis of the chemosensitizing effect of curcumin on CRC cells treated with 5-FU - Yang, Jingbo; He, Chengyan; Liu, Ning (Frontiers in Medicine, 2022)
Background: 5-Fluorouracil (5-FU) is one of the most common chemotherapy drugs used to treat colorectal cancer (CRC), which often develops resistance in more than 15% of patients. curcumin, an active component of Curcuma longa, has been reported to have antitumor activity for CRC, and furthermore, to enhance the effect of chemotherapy against colorectal cancer cells. However, the molecular mechanisms underlying the sensitizing effect of curcumin to 5-FU have not been largely elucidated. In this study, we aim to systematically investigate the role of curcumin as a chemosensitizer for treatment of CRC, along with the key events responsible to its pharmaceutical effect, which may lead to better clinical outcomes. Methods: A high-resolution 2DE-based proteomics approach was used to characterize global protein expression patterns in CRC cells treated with 5-FU, in combination with or without curcumin. The differentially expressed proteins were obtained from the 2DE analysis, which were subsequently identified by MALDI-TOF MS or nano-ESI-MS/MS, some of which were validated by western blot. Intracellular reactive oxygen species (ROS) was measured to assess the change of redox environment resulted from the drug treatment. Results: A series of proteins with altered abundances were detected and identified by MALDI-TOF or nano-MS/MS. From a total of 512 isolated proteins, 22 proteins were found to be up-regulated, and 6 proteins were down-regulated. Intracellular ROS was significantly elevated after curcumin treatment. Furthermore, mass spectrometry data revealed that some of the proteins appeared to have more oxidized forms upon curcumin treatment, suggesting a direct evidence of role ROS in chemosensitizing effect of curcumin. Conclusions: The effect of curcumin in enhancing chemosensitivity to 5-FU is a complex phenomenon undergoing several mechanisms including enhancement of intracellular level of ROS. Our findings presented here could provide clues to further study for elucidating the mechanisms underlying chemosensitizing effect of curcumin.